Ragam Sumber Pendapatan Petani Padi Sawah di Kalimantan Tengah: Studi Kasus di Kabupaten Kotawaringin Timur dan Kabupaten Kapuas - Sayaka, Bambang; Hutabarat, Budiman (Jurnal Agro Ekonomi, 1996)
Rice farmers in districts of Kotawaringin Timur and Kapuas (Central Kalimantan Province) earn their main income from agricultural sector, each of 87 percent and 70 percent, respectively. Income distribution of farmers in both districts is well circulated relatively. Income proportions achieved by 40 percent of lowest income group in the districts of Kotawaringin Timur and Kapuas are 14 percent and 17 percent, and their Gini coefficients are 0.4144 and 0.4052, respectively. Unbalanced income distribution in Kotawaringin is affected more by agricultural earnings than that of non agricultural sector. Reducing the unbalanced distribution of farmers income is possible done by increasing income sources generated from upland farming and non agricultural sectors.